Politics and the issue of “cantegriles” during the neobatllismo: poverty and discrimination (1955-1960) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This work describes and analyzes the evolution of “cantegriles” montevideanos into an urban subject reachable and identifiable in the city by technicians and government authorities. This transformation was influenced by the government’s “panamericanism”, as it was in Pan-American organs and guidelines where it found a solution to the problem of “cantegriles”, barely known by Uru- guayan academia at that time. From then on, an area of Montevideo and its inhabitants were characterized and stigmatized, ge- nerating processes of urban segregation since the mid-twentieth century, in a country that saw itself as a hyper-integrated society.
Keywords: Cantegriles; Readjustment; Discrimination; Poverty.